1998
DOI: 10.1007/bf02475254
|View full text |Cite
|
Sign up to set email alerts
|

1H mas NMR study of OH groups in the AlPO4/SiO2 system

Abstract: Three solids of composition SiO2, AIPO4 and 20:80 mol/mol A1PO4/SiO2, respectively, were synthesized. Their textural properties were examined and 1H MAS NMR spectroscopy was used to characterize their surface OH groups. The results reveal that the solids are amorphous and texturally suitable for use as catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…As noted earlier, the former corresponds to Mg-OH groups, whereas the latter is due to Si-OH groups in the amorphous, fibrous silica structure obtained by effect of the acid pretreatment. This chemical shift at 1.9 ppm is similar to that reported by our group and other authors for amorphous silica of variable nature (27)(28)(29). Finally, solid SP-G4 exhibits a single signal, at 1.9 ppm, corresponding to Si-OH groups in the silica.…”
Section: Characterization Of the Supportssupporting
confidence: 84%
“…As noted earlier, the former corresponds to Mg-OH groups, whereas the latter is due to Si-OH groups in the amorphous, fibrous silica structure obtained by effect of the acid pretreatment. This chemical shift at 1.9 ppm is similar to that reported by our group and other authors for amorphous silica of variable nature (27)(28)(29). Finally, solid SP-G4 exhibits a single signal, at 1.9 ppm, corresponding to Si-OH groups in the silica.…”
Section: Characterization Of the Supportssupporting
confidence: 84%
“…MgO is known as ceramic oxide and is used as a catalyst and a support material for some metal catalysts and also in the manufacturing of high temperature superconductors [13]. It has been reported that, MgO-precursor affects the catalytic properties of metal oxides supported on it [6][7][8]11,[14][15][16]. MgO is usually produced for commerce by thermal decomposition of magnesite MgCO 3 and from magnesium hydroxide obtained from sea water treatment [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…MgO is usually produced for commerce by thermal decomposition of magnesite MgCO 3 and from magnesium hydroxide obtained from sea water treatment [17,18]. Using various precursors for MgO as Mg(OH) 2 , Mg(NO 3 ) 2 , MgCl 2 , MgCO 3 and magnesium acetate affect the basic nature of the catalyst surface and this is reflected on the catalytic activity of the solid catalyst [11,15,16]. Mg(NO 3 ) 2 is used as a precursor for MgO support in hydrocarbon synthesis [14] and oxidation of cyclo-hexanone with H 2 O 2 and benzonitrile [6].…”
Section: Introductionmentioning
confidence: 99%
“…María and co workers reported that the Cu-Mg-Al catalyst exhibit complete conversion in the liquid phase transfer hydrogenation of FU using isopropanol as hydrogen donor [17]. So in this contest, MgO and Mg-Al catalysts have been reported for the catalytic transfer hydrogenation of cyclohexanone to cyclohexanol by using isopropanol as hydrogen donor [18,19]. Additionally MgO/M 2 O 3 (M=Al, Ga, In) shows activity towards the CTH of α, β-unsaturated aldehydes [20].…”
Section: Introductionmentioning
confidence: 94%